Effects of balance training combined with stroboscopic visual training on balance ability in college-aged male soccer players - Maochun Lu; Yuan Zhai; Hui Peng; Junsheng Cao; Yi Yang; Liang Chen (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background Balance training combined with stroboscopic visual training (SVT) has emerged as a potential intervention for enhancing athletic performance. However, limited evidence exists regarding its effectiveness on soccer players’ balance abilities. This study aimed to investigate the effects of a 12-week SVT combined with balance training program on balance ability in college-aged male soccer players. Methods Thirty male soccer players (aged 18–22 years) were randomly assigned to either an experimental group (SVT + balance training, n = 15) or a control group (traditional training, n = 15). Balance assessments were conducted pre- and post-intervention using the Stork Stand Balance Test (SSBT), Static Single Stance Test (ST), Y-Balance Test (YBT), Sensory Organization Test (SOT), Motor Control Test (MCT), and Adaptation Test (ADT). The experimental group underwent thrice-weekly training sessions combining SVT (3 Hz frequency) with progressive balance exercises. Results Significant improvements were observed in the experimental group compared to the control group across multiple parameters (p < 0.05). The experimental group demonstrated superior performance in SSBT (Cohen’s d = 3.431), ST under eyes-closed conditions (d = 1.318), YBT for both dominant (d = 2.582) and non-dominant legs (d = 3.699), SOT composite score (d = 1.579), and ADT toes-down condition (d = 1.581). Additionally, significant enhancements were noted in visual (VIS) and vestibular (VEST) indices of the SOT. Conclusion The 12-week balance training combined with SVT significantly improved static and dynamic balance abilities in college-aged male soccer players, particularly under visually challenging conditions. This integrated training approach may provide an effective strategy for enhancing balance control in soccer players. Trial registration number Chinese Clinical Trial Registry (ChiCTR2500103857). Registered 06 June 2025 (Retrospectively registered).